Catalogue of type specimens of invertebrates in the collection of the Instituto Nacional de Pesquisas da Amazônia, Manaus, Brazil. II. Hexapoda: Collembola, Diplura, Archaeognatha, Ephemeroptera and Blattaria - Ribeiro,José Moacir Ferreira (Sociedade Brasileira De Entomologia, 2008)
A catalogue of type specimens of Collembola, Diplura, Archaeognatha, Ephemeroptera, and Blattaria deposited in the Invertebrate Collection of the Instituto Nacional de Pesquisas da Amazônia (INPA), Manaus, Brazil, is presented and updated to June, 2007. It contains a total of 22 holotypes and 18 lots of paratypes of 22 species of Collembola; one holotype and one paratype of one species of Diplura; four holotypes and four paratypes of four species of Archaeognatha; 10 holotypes and thirteen lots of paratypes of 11 species of Ephemeroptera; and one holotype and two lots of paratypes of one species of Blattaria. Specific names are listed alphabetically within family, followed by bibliographical citation, original genus name, status of type, collection number and locality data.